(untitled) (Research, Society and Development, 2021)
In 2017, the Brazilian National Congress converted Provisional Measure No. 759 (MP 759) into Law No. 13,465, dictated by the Federal Government, whose text deals, among other topics, with rural and urban landowners and on land regularization within the Legal Amazon. This legislation has been the target of strong criticism by various social movements and entities linked to the struggle for land, both for its possible unconstitutionalities and for the weakening of public policies established in recent decades, as they claim that this is, among several points, a law that benefits the speculative real estate market, land grabbing and land reconcentration from agrarian reform. The purpose of this article is to bring to the debate some historical and recent elements about the struggle for land in Brazil, as well as to discuss the possible effects and repercussions of the referred Law, especially in the scope of the agrarian reform policy in Brazil.